Tantangan demokrasi di Indonesia di era digital - Prayoga, Imam Lipi (Maliki Interdisciplinary Journal, 2026)
The advancement of information and communication technology has fundamentally transformed the political landscape of Indonesia, including how democracy is practiced and perceived by citizens. This study examines three main dimensions: the development of Indonesian democracy in the digital era, identification of challenges posed by digital technology and social media, and the roles of civil society, the government, and the media in safeguarding democratic quality. Using a qualitative approach with a library research method, this study reviews academic literature, regulations, and relevant empirical documentation. The findings indicate that the digital space opens broader participation opportunities while simultaneously presenting threats including disinformation, opinion polarization, political manipulation, and a decline in deliberative culture. Collective synergy among all elements of society is essential to ensure digital technology serves as an instrument for strengthening Pancasila democracy rather than undermining it.